Knowledge creation as a source of competitive advantage: Evidence of FMCG firms in nigeria - Michael Segun Ogunmuyiwa; Ferdinand Ikechukwu Muo; Shafi Abidemi Adewoyin (Economic Review: Journal of Economics and Business, 2023)
This study examines the nexus between knowledge creation and organization competitiveness of Fast Moving Consumer Goods (FMCGs) firms in Nigeria, with special focus on Lagos and Ogun State, Nigeria. The study employed a survey research design, through the administration of structured questionnaire to employees of some selected FMCGs. Through its empirical findings of a positive and significant relationship, the study provides evidence that knowledge creation plays an important role in organization competitiveness of FMCGs in Nigeria. Thus, it is evident that, knowledge creation is an important driver of organizational competitiveness of FMCGs firms in Nigeria. In line with the empirical findings, it is recommended that FMCGs should employ knowledge creation to enhance competitiveness of FMCGs and the entire manufacturing sub sector in Nigeria.
Keywords: D8; D83; L22; L23; M10; 330; knowledge creation; knowledge management; organisation competitiveness